Influence of anti-allergic drugs used systemically on the process of root resorption during delayed tooth replantation: A study in rats - Machado, Nathália Evelyn da Silva [UNESP]; Banci, Henrique Augusto [UNESP]; da Silva, Lucas Deszo; Santinoni, Carolina dos Santos; de Oliveira, Danilo Louzada; Ervolino, Edilson [UNESP]; Prado, Rosana Leal do; Mori, Graziela Garrido (Wiley, 2020)
Background/Aim: Anti-allergic drugs can inhibit the hard tissue resorption process, and due to similarities between root resorption and bone mechanisms, it can be inferred that these drugs may also control root resorption. The aim of this study was to analyze the effects of anti-allergic drugs used systemically on the process of root resorption following delayed tooth replantation. Materials and Methods: Thirty-two maxillary right incisors of rats were extracted and subsequently replanted. Rats were divided into four groups according to the anti-allergic drug administered: the rats in groups DEX, Q, and MO were treated systemically with dexamethasone phosphate, quercetin, and montelukast, respectively, and no systemic medication was administered to rats in group C. After 60 days, the animals were euthanized, and the specimens were processed for histomorphometric and immunohistochemical analyses. Statistical significance was set at P <.05. Results: There were no significant differences between the groups in terms of inflammatory resorption, replacement resorption, or presence of tartrate-resistant acid phosphatase. In terms of events occurring in the periodontal ligament space, there was a difference between groups Q and MO due to the presence of dental ankylosis and inflammatory connective tissue (P <.05). A difference in inflammatory cells was also observed through CD45 immunolabeling between the DEX and Q groups when compared to the C group (P <.05). Conclusion: The systemic administration of anti-allergic drugs did not have an effect on the process of root resorption following delayed tooth replantation.
Keywords: anti-allergic agents; root resorption; tooth replantation